Green HRIS: Innovating Human Resource Information Systems to Promote Sustainable HR Practices in the ESG ((Environmental, Social, and Governance) - Mia Kusmiati; Avinash Pawar; Asep Gema Nurochmat; Hari Imbrani; M. Syahrudin; Iwan Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to analyze the strategic role of the Green Human Resource Information System (Green HRIS) in bridging the transformation of human resource management with the demands of Environmental, Social, and Governance (ESG) principles, specifically examining how Green HRIS contributes to sustainable HR practices, organizational performance, and digital HR transformation. Using a Systematic Literature Review (SLR) approach, this study identifies, evaluates, and synthesizes prior research by conducting a structured search across major academic databases—Scopus, Web of Science, Springer, Elsevier, and Wiley—for publications from 2020 to 2025 that address green HRM, HR digitalization, sustainable HR practices, and ESG integration. The review process includes screening titles, abstracts, and full texts, extracting key data, and categorizing findings into environmental, social, and governance dimensions. The results demonstrate that Green HRIS strengthens ESG implementation by reducing paper usage, lowering carbon emissions, and promoting sustainable HR practices such as digital recruitment and e-learning, while also improving governance through enhanced transparency, accountability, regulatory compliance, and real-time reporting. Empirical evidence indicates that Green HRIS fosters employee engagement, organizational innovation, and the development of green competitive advantages. Practically, the study highlights how organizations, policymakers, and HR managers can utilize Green HRIS to optimize digital transformation and meet ESG requirements, thereby reinforcing legitimacy and long-term competitiveness within the green economy. This research offers originality as one of the first systematic reviews addressing Green HRIS in the ESG era, integrating theories such as the Resource-Based View, Technology Acceptance Model, and organizational sustainability theory, while also mapping trends, best practices, and gaps for future research.